EVOLUTION OF ECONOMIC MANAGEMENT: THE INFLUENCE OF SERVICE QUALITY ON BEHAVIORAL INTENTION - Yohana; Budi Prasetyo; Bondan Subagyo (Adisam Publisher, 2024)
The development of economic management demonstrates a greater awareness of the relationship between consumer behavioral intentions and service excellence. Businesses can provide better customer service and boost positive word-of-mouth and economic performance by implementing a customer-centric approach and utilizing contemporary technologies. The impact of service quality on the intents of conduct in economic management has become an interesting research focus. Based on several research results conducted, there are several findings that can provide insight into the connection between behavioral intentions and service excellence. Good service quality is key to creating and maintaining positive behavioral intentions among customers. By understanding and managing the dimensions of service quality, companies can increase long-term success is influenced by a number of factors, including favorable word-of-mouth, client happiness, and loyalty in economic management.